ANALISIS KUALITAS AIR SUMUR GALI BERDASARKAN INDEKS PENCEMARAN SERTA PERSEPSI DAN PERILAKU MASYARAKAT DI DESA SANUR KAUH DENPASAR SELATAN - Kahar, Gertrudis Vebriyanti; Sudiana Mahendra, Made; Mahardika, I Gede (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 16 No 1 (2022)DO - 10.24843/EJES.2022.v16.i01.p06, 2022)
The goal of the study was to analyze the water quality of dug wells based on Bali Governor Regulation No. 16 of 2016 and Regulation of the Minister of Health of the Republic of Indonesia No.492/Menkes/Per/IV/2010, which analyzes the quality status of dug well water and its distribution based on the Pollution Index (IP) value and community behavior in Sanur Kauh Village, South Denpasar. Purposive sampling at three stations with three repeats was used to determine the sample. Temperature, color, taste, odor, TDS, turbidity, pH, DO, BOD, COD, Nitrate (NO3-N), Phosphate (PO4), Chloride (Cl-), Iron (fe), E. Coli, and total coliforms were among the parameters measured in situ and ex situ (laboratory). Questionnaires and interviews with respondents who used dug well water were used to collect data on perception and behavior of components (households, business actors and/or activities, farmers, and the government), which were analyzed using a Likert scale and binary model. Surfer and GIS were used to map the water from an excavated well. The results of the analysis of the quality of dug well water exceeded the Class I Water quality standard set by Bali Governor Regulation No. 16 of 2016 for BOD, COD, phosphate, nitrate, iron, total coliform, and turbidity parameters, as well as the Indonesian Minister of Health Regulation No.492/Menkes /Per/IV/2010 for BOD, COD, phosphate, nitrate, iron, total coliform, and turbidity parameters Population activities, pollution sources, climate, soil type and topography, height and depth of the well all influence the water quality status of dug wells, which is classified as moderately polluted. The average community's impression of the provision of dug well water, water pollution, and waste management is positive, and the average community conduct is positive. Keywords: Shallow Groundwater, Groundwater Quality, Quality Status, Perception, Behavior